Financial balance of small independent hotels: the management view - Alves, Diana Vieira (2021)
In order to succeed in a competitive tourism world, financial balance is fundamental to hotel management. In the particular case of small independent hotels , the financial ratios and indicators analysis have been used connected with the decision-making process, which allows their survival. Prior studies related to the use of financial ratios and indicators in the hospitality industry in several countries has demonstrated that these analysis are one of the most important management tools. Hotel chains normally use global financial ratios and indicators, which provide a huge amount of information. That can be explained by the fact that they have to follow management worldwide rules. However, as in many European countries, the Portuguese corporate structure is composed by micro and small enterprises. This fact has led us to porpose a set of suitable financial ratios and indicators (liquidity, solvency, profitability, and turnover ratios and indicators) - "tableau de bord" - to be used on smal independent hotels' management. A questionnaire addressed to independent hotel managers was conducted to obtain data, which has been submitted to a statistical analysis. To characterize the finacial ratios and indicators descritpive statistics were used. The conclusion shows that despite the importance of some of the financial ratios and indicators they are not being used, which indicates an opportunity related to the proposal of a "tableau de bord" adapted to small independent hotels management.